Some notes on cognitive dynamic: inspired by v. Bozickovic’s the indexical point of view - Corazza, Eros (2023)
Bozickovic’s The Indexical Point of View is a rich and well-argued book in which he raises many interesting questions regarding indexical reference. In what follows I will mainly concentrate on Bozickovic’s neo-Fregean proposal and the criticism he proposes to the Kaplan-Perry theory according to which characters are what help us to handle the cognitive significance problem. Although I think Bozickovic’s account to be accurate, the criticisms he raises against Perry may be dealt with without having to dismiss the Kaplan-Perry framework.